2012
DOI: 10.1111/j.1526-4637.2011.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Advancing a National Agenda to Eliminate Disparities in Pain Care: Directions for Health Policy, Education, Practice, and Research

Abstract: Recent national legislative initiatives within ACA are expected to generate multilevel efforts that will impact the flow of funding to address the pervasive issue of disparities. It is an opportune time for the pain community to take a lead in implementing a concerted agenda on pain care disparities in order to leverage these national initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(79 citation statements)
references
References 115 publications
1
77
0
1
Order By: Relevance
“…5 There is also evidence of systematic variability in prescribers' choices of analgesics according to patient race or ethnicity. [7][8][9][10][11] In a recent meta-analysis 10 that synthesized data on analgesic treatment disparities…”
Section: Introductionmentioning
confidence: 99%
“…5 There is also evidence of systematic variability in prescribers' choices of analgesics according to patient race or ethnicity. [7][8][9][10][11] In a recent meta-analysis 10 that synthesized data on analgesic treatment disparities…”
Section: Introductionmentioning
confidence: 99%
“…Our findings raise the broader question of whether efforts to address racial disparities in pain should focus on reducing disparities in opioid prescription, as has been suggested in prior policy recommendations [3]-at least in the case of patients with chronic noncancer pain. The use of race in decisions to prescribe opioids is clearly inconsistent with good medical practice and arguably constitutes racial bias.…”
Section: Discussionmentioning
confidence: 61%
“…Unfortunately, studies conducted in various settings, including the VA, have shown that primary care providers find chronic pain patients to be frustrating and difficult to treat and do not feel adequately prepared to provide care for them [42][43]. The growing movement toward "patient-centered medical homes," which are based on principles of accessibility, continuity, and care coordination, provides an opportunity for more effective and equitable chronic pain care [3,44]. However, because these models center on the role of primary care providers, it is critical that these providers have training in chronic pain treatment overall and in providing equitable care [3].…”
Section: Blacks Whites Blacksmentioning
confidence: 99%
See 2 more Smart Citations